The flow of art : essays and criticisms - McBride, Henry, 1867-1962 (New Haken : Yale University Press, 1997)
First published 1975 by Atheneum Publishers, reissued with new forwa rd 1997
Includes index
Keywords: Art; Art criticism -- United States; Art critics -- U.S.; Rich, Daniel Catton, -- 1904-